2020
DOI: 10.1177/0018726720933317
|View full text |Cite
|
Sign up to set email alerts
|

The dimensional structure of transparency: A construct validation of transparency as disclosure, clarity, and accuracy in organizations

Abstract: In this article, we advance research on transparency by developing and validating a measure based on recent theoretical insights about its dimensionality. We find that transparency—defined as the perceived quality of information—is a three-dimensional construct consisting of perceived information disclosure, clarity, and accuracy. Evidence shows items associated with these dimensions can be aggregated into a single transparency construct. We also find that transparency (as an aggregate construct) is distinct f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 120 publications
(141 reference statements)
2
70
1
Order By: Relevance
“…This may be due to the peculiarities of the COVID-19 pandemic, as people likely became used to constantly encountering new complex information and thus accepted a lower level of information lucidity. Despite the missing effect between clarity and initial trust, our findings are consistent with the existing transparency-trust literature [ 51 , 62 , 63 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This may be due to the peculiarities of the COVID-19 pandemic, as people likely became used to constantly encountering new complex information and thus accepted a lower level of information lucidity. Despite the missing effect between clarity and initial trust, our findings are consistent with the existing transparency-trust literature [ 51 , 62 , 63 ].…”
Section: Discussionsupporting
confidence: 91%
“…Transparency perceptions are essential as they form the basis for active and passive information-seeking strategies. By using the recent DCA-transparency scale [ 63 ], we further elaborated on the role of transparency (ie, information quality) in URT as proposed by Venkatesh et al [ 28 ]. Finally, it was shown that trust transfer theory holds true in the investigated setting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations